2020
DOI: 10.1103/physrevlett.124.215301
|View full text |Cite
|
Sign up to set email alerts
|

Angular Momentum in Rotating Superfluid Droplets

Abstract: FIG. 3. Calculated equilibrium density profiles of a deformable 4 He cylinder rotating around its symmetry axis at fixed L SF =N He ¼ 7.83ℏ for different numbers of vortices. Streamlines are shown in black. The positions of the vortex cores are marked by red dots for visualization. The color bar shows the density in units of Å −3 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 37 publications
(74 reference statements)
8
68
1
Order By: Relevance
“…The diffraction patterns are recorded at small scattering angles and, thus, predominantly contain information on the column density of the droplets in the direction perpendicular to the detector plane. 4 He droplets [11,14,16,17]. Spheroidal and prolate shapes result from centrifugal deformation of droplets with considerable angular momentum.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The diffraction patterns are recorded at small scattering angles and, thus, predominantly contain information on the column density of the droplets in the direction perpendicular to the detector plane. 4 He droplets [11,14,16,17]. Spheroidal and prolate shapes result from centrifugal deformation of droplets with considerable angular momentum.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described for 4 He droplets [11,[14][15][16][17], we ascribe the shape deformation in 3 He droplets to centrifugal distortion. It has been reported that the shapes of rotating 4 He droplets closely follow the equilibrium shapes of classical droplets having the same values of angular momentum [14,16,17,20,21]. This pattern is also expected to be the case of 3 He droplets, which at the temperature of these experiments (∼0.15 K) [29] should behave classically due to the high viscosity of about 200 µP and small mean free path (a few nanometers) of elementary excitations at this temperature [32].…”
Section: Average Angular Momenta and Angular Velocities Of 3 He Anmentioning
confidence: 99%
See 3 more Smart Citations